Consistency and Harmony in the Arabic Textbook for the 10th Grade of Secondary School Published by the Ministry of Religious Affairs of the Republic of Indonesia/ الاتساق والانسجام في النصوص المقروءة في الكتاب المدرسي للفصل العاشر للمدرسة الثانوية نشرته وزارة الشؤون الدينية للجمهورية الإندونيسية - Fikha Ilma Hayati Rukmana; Moh. Ainin; Nurhidayati Nurhidayati (Universitas Negeri Malang, 2022)
This research aims to describe the consistency and harmony in the Arabic textbook for the tenth semester of the secondary school of the Bulletin of Religious Affairs of the Republic of Indonesia. This research uses discourse analysis in the qualitative descriptive method. The data sources in this research mean the textbook for the tenth semester of secondary school which was published in the Religious Affairs Bulletin of the Republic of Indonesia in 2019. The results of this research are 1) the consistency in the texts means referral, substitution, omission, conjunction, repetition, synonym, and inclusion, and 2) The consistency in texts is the linguistic aspects and the details of the content of the paragraph. يهدف هذا البحث لوصف الاتساق في النصوص المقروءة في الكتاب الدراسي للفصل X للمدرسة الثانوية نشرة الشؤون الدينية للجمهورية الإندونيسية، و لوصف الانسجام في النصوص المقروءة في الكتاب الدراسي للفصل العاشر للمدرسة الثانوية نشرة الشؤون الدينية للجمهورية الإندونيسية. يستحدم هذا البحث طريقة تحليل البحث، يعني وصفي كيفي بمنهج تحليل الخطاب. و مصادر البيانات في هذا البحث يعني الكتاب الدراسي للفصل العاشر للمدرسة الثانوية الذي نشرة الشؤون الدينية للجمهورية الإندونيسية 2019. و النتائج في هذا البحث هي 1) يظهر الاتساق في النصوص يعني الاحالة و الاستبدال و الحذف و العطف و التكرار و المرادف و الاشتمال، 2) الانسجام في النصوص هو الجوانب اللغوية و تفاصيل محتوى الفقرة.